Meningkatkan Pengalaman Belajar Mahasiswa di Ubhara Jaya Melalui Sistem Evaluasi Pembelajaran Olahraga: Studi Pendahuluan - Pasaribu, Ahmad Muchlisin Natas (Universitas Pendidikan Ganesha, 2024)
This study aims to investigate the impact of the use of sports learning evaluation systems on students' learning experiences at Bhakti Harapan Jaya University (Ubhara Jaya). The research is conducted as an effort to improve and enhance the process of sports learning among students. This research method involves an initial survey of selected respondents to collect data on their perceptions of the use of evaluation systems in sports learning. The survey results show a positive trend in enhanced learning experiences through the use of this system. These findings provide valuable insights into the potential development of sports learning evaluation systems in the higher education environment. The implications of this research can open opportunities for the integration of technology in sports teaching, providing a basis for further development related to the use of evaluation systems and similar tools to enhance the quality of sports learning in educational institutions.